Columnar Gd2O3:Eu3+/Tb3+ phosphors: preparation, luminescence properties and growth mechanism. Issue 45 (5th November 2018) - Qian, Benfu; Zou, Haifeng; Meng, Deyue; Zhou, Xiuqing; Song, Yanhua; Zheng, Keyan; Miao, Chong; Sheng, Ye
Abstract : Columnar Gd2 O3 :Eu 3+ /Tb 3+ phosphors were successfully prepared by a solvothermal method and subsequent calcination process. Abstract : Columnar Gd2 O3 :Eu 3+ /Tb 3+ phosphors were successfully prepared by a solvothermal method and subsequent calcination process. The structure, morphology and luminescence properties of the as-prepared products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and photoluminescence (PL) spectra. The XRD results indicate that the precursor sample is hexagonal Gd(OH)3 while the calcinated sample is cubic Gd2 O3 . SEM and TEM images show that both the precursor and the calcined samples are columnar, with lengths of 220 nm and 214 nm and diameters of 130 nm and 126 nm, respectively. The fluorescence spectrum shows that Gd2 O3 :Eu 3+ generates a characteristic red emission when stimulated by ultraviolet light with a wavelength of 250 nm, which corresponds to the 5 D0 → 7 F2 transition of Eu 3+ . Gd2 O3 :Tb 3+ generates a characteristic green emission when stimulated by ultraviolet light with a wavelength of 240 nm, which corresponds to the 5 D4 → 7 F5 transition of Tb 3+ .